Preparation method and application of high-temperature-resistant conjugated crystal material of bis-imidazole-substituted terephthalonitrile
Patent Information
- Application Number
- CN202611086094.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-09
AI Technical Summary
[0022]本发明以联咪唑与四氟对苯二腈为原料,原料简单且商业易获取,通过一步溶剂热反应即可制备有机晶体材料;合成过程无需对原料进行复杂预处理,反应条件温和,工艺流程简化;所得材料在反应结束后仅需分离洗涤即可获得,避免了其他有机半导体材料复杂的制备和纯化过程。所获得的材料具有片状晶体结构、半导体能带特征、优异的空气热氧化稳定性和光热转换性能,可作为有机半导体材料、光热涂层、耐热涂层、阻燃填料和高耐热复合材料填料等应用。
Smart Images

Figure CN122878263A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic functional crystal materials and conjugated molecule synthesis technology, and particularly relates to a method for preparing and applying a high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material. Background Technology
[0002] Organic conjugated crystal materials are typically formed by the orderly assembly of conjugated organic molecules through π–π stacking, dipole interactions, or other weak interactions. These materials exhibit high crystallinity and well-defined molecular arrangements, enabling the formation of ordered electron transport channels to a certain extent. Therefore, they have wide applications in fields such as organic field-effect transistors, photodetectors, organic solar cells, flexible electronic devices, and photothermal conversion.
[0003] However, some existing organic semiconductors or photothermal materials are prone to decomposition, oxidation, or structural rearrangement under high temperature, air, or strong light conditions, leading to a decline in material performance and limiting their further application in high-temperature photothermal conversion, thermal protective coatings, flame-retardant materials, and high-temperature electronic devices. Therefore, it is still necessary to develop a nitrogen-rich conjugated organic crystal material that combines a simple synthesis route, high crystallinity, wide light absorption characteristics, semiconductor band structure, and high thermal stability.
[0004] Biimidazole is a class of nitrogen-rich aromatic heterocyclic compounds containing two imidazole rings. The molecule contains multiple nitrogen atoms and N–H reaction sites, which have a certain coordination ability. It can undergo nucleophilic substitution or coupling reactions with aromatic compounds containing active halogens, thereby constructing a variety of nitrogen-rich conjugated structural systems.
[0005] Based on these properties, biimidazole and its derivatives have been used to construct organic semiconductor materials, coordination polymers, and organic crystal functional materials. Nitrogen-containing aromatic heterocyclic structures typically possess a certain degree of electronic modulation capability, which can regulate molecular energy level structure and enhance intermolecular interactions, thereby affecting the photoelectric properties and thermal stability of the materials. Therefore, this type of conjugated crystal material containing a rigid aromatic framework and a nitrogen-rich structure has application potential in photoelectric conversion, sensing, catalysis, and heat-resistant functional materials, and may exhibit certain thermal stability and char residue characteristics, making it suitable for high-temperature resistant functional materials or coating systems. Summary of the Invention
[0006] The technical problem to be solved by this invention is to address the issues of high preparation cost, complex process flow, insufficient thermal stability and application adaptability of existing organic conjugated crystal materials, and to propose a high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material, its preparation method and application.
[0007] To address the aforementioned technical problems, this invention provides a method for preparing a high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material, comprising the following steps:
[0008] Biimidazole and tetrafluoroterephthalonitrile in a molar ratio of 0.5:1 to 4:1 are added to a solvent for a solvothermal reaction, wherein the total mass of the solute is 0.5% to 5% of the mass of the solvent.
[0009] After the reaction was completed, the mixture was cooled to room temperature, the supernatant was removed, the precipitate was collected, washed with solvent, and dried to obtain a bisimidazole-substituted terephthalonitrile conjugated crystal material.
[0010] When biimidazole is thermally reacted with tetrafluoroterephthalonitrile, the NH site in biimidazole can undergo substitution or coupling reactions with the Ar-F bond in tetrafluoroterephthalonitrile, accompanied by the removal of hydrogen fluoride or fluoride ions. Since both monomers possess multifunctional structures, a multi-point connected nitrogen-rich aromatic heterocyclic conjugated framework can be formed during the reaction. The products further accumulate and crystallize through intermolecular π-π interactions, hydrogen bonds, or dipole interactions to form crystalline materials.
[0011] In a preferred embodiment of this scheme, the solvent is N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP).
[0012] In a preferred embodiment of this scheme, the reaction temperature of the solvothermal reaction is 100-200℃, and the reaction time is 4-20 hours.
[0013] The reaction needs to be carried out at a specific temperature to promote the dissolution, diffusion, and coupling of biimidazole and tetrafluoroterephthalonitrile in the solvent. While lower temperatures favor slow crystal growth, the yield is lower. Higher temperatures significantly promote the coupling reaction and increase the yield, resulting in larger crystal particles. Appropriately increasing the solute concentration can improve the number of nuclei and the yield, but excessively high concentrations limit crystal growth space, easily leading to the formation of small, irregularly shaped crystals.
[0014] Under suitable reaction time, concentration, and temperature conditions, the reaction rate, nucleation rate, and reversible equilibrium are optimally balanced during crystal growth, resulting in a high reaction conversion rate and the acquisition of materials with large particle size and high crystallinity.
[0015] Furthermore, alkaline organic additives can interact with reactants or intermediates through acid-base reactions, hydrogen bonding, or coordination, thereby regulating the coupling reaction rate, molecular mobility, and crystal arrangement. This allows for controllability in the composition, crystal structure, thermal stability, and color appearance of the products. By adjusting these conditions, materials with different semiconductor properties, photothermal conversion properties, and temperature resistance can be obtained.
[0016] In a preferred embodiment of this scheme, an organic auxiliary agent is also added during the solvothermal reaction to regulate the crystal morphology, molecular packing and thermal stability of the material. The organic auxiliary agent is one or more of pyridine, triethylamine, ammonia, imidazole, dimethylimidazolium, quinoline and piperidine.
[0017] By adjusting the solvent, additives, concentration, and reaction temperature, the solute solubility, reaction rate, nucleation rate, and stacking efficiency can be controlled to obtain materials with different morphologies and properties.
[0018] According to the above-mentioned method for preparing high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal materials, the prepared bisimidazole-substituted terephthalonitrile conjugated crystal materials have a dark (brown to dark green) appearance, multispectral absorption performance, semiconductor band characteristics, excellent thermal stability, air thermal oxidation stability and rapid photothermal conversion performance, and are plate-like crystals or layered stacked structures, and only show significant thermal oxidation weight loss at temperatures above 500 °C in air atmosphere.
[0019] Furthermore, bisimidazole-substituted terephthalonitrile conjugated crystal materials are applied in the fields of organic semiconductors, photoelectric detection, photothermal conversion, solar thermal utilization, heat-resistant coatings, flame-retardant fillers, or heat-resistant composite materials.
[0020] The high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material prepared in this invention possesses a highly conjugated π-electron system composed of multiple aromatic heterocycles, exhibiting a high degree of intramolecular electron delocalization and suitable energy level structure and semiconductor band characteristics. Simultaneously, this material exhibits good crystallinity and a layered stacking structure, which is beneficial for carrier transport, thus it can be used as an organic semiconductor material in fields such as organic field-effect transistors, optoelectronic devices, sensors, and flexible electronic devices. Due to its donor-acceptor (DA) conjugated structure and large π-conjugated system, this material has a wide absorption range for visible and near-infrared light, and the absorbed light energy can be efficiently converted into heat energy through non-radiative transitions. Therefore, it can be applied in fields such as photothermal conversion, solar thermal utilization, photothermal heating, photothermal catalysis, and photothermal therapy. Because this material has a rigid conjugated aromatic heterocyclic skeleton, high nitrogen content, and abundant intermolecular π-π interactions, it possesses high thermal and structural stability. Adding it to a polymer matrix can improve the thermal stability, heat resistance, and mechanical properties of the composite material, making it suitable for high-temperature resistant composite materials, functional coatings, flame-retardant fillers, and engineering plastics.
[0021] Implementing this invention has the following beneficial effects:
[0022] This invention uses biimidazole and tetrafluoroterephthalonitrile as raw materials, which are simple and commercially available. Organic crystalline materials can be prepared through a one-step solvothermal reaction. The synthesis process requires no complex pretreatment of the raw materials, the reaction conditions are mild, and the process flow is simplified. The obtained material only needs to be separated and washed after the reaction, avoiding the complex preparation and purification processes of other organic semiconductor materials. The obtained material has a plate-like crystal structure, semiconductor band structure, excellent air-thermal oxidation stability, and photothermal conversion performance. It can be used as an organic semiconductor material, photothermal coating, heat-resistant coating, flame-retardant filler, and high-heat-resistant composite material filler. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 Photographs of the materials in Examples 2 / 4 / 6;
[0025] Figure 2 Scanning electron microscope images of the materials in Examples 1-6;
[0026] Figure 3 Optical microscope photographs of the materials in Example 2;
[0027] Figure 4 The lattice band structure of the material in Example 2 is shown in the calculation diagram.
[0028] Figure 5 The X-ray diffraction patterns and thermogravimetric analysis diagrams under nitrogen / air for the materials in Examples 2 / 4 / 6 are shown.
[0029] Figure 6 These are ultraviolet thermal imaging images of the materials in Examples 2 / 4 / 6;
[0030] Figure 7 UV-Vis ablation images of the materials in Examples 2 / 4 / 6 at 9W for 5 minutes. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Example 1
[0033] Bimidazole powder (1 mmol) and tetrafluoroterephthalonitrile powder (1 mmol) were added to a reaction vessel containing 50 g of DMF solvent and reacted at 120 °C for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the precipitate was washed three times with DMF and dried to obtain 0.005 g of powder.
[0034] Example 2
[0035] Bimidazole powder (2 mmol) and tetrafluoroterephthalonitrile powder (2 mmol) were added to a reaction vessel containing 50 g of DMF solvent and reacted at 160 °C for 10 hours. After the reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, the precipitate was washed three times with DMF, and then dried to obtain 0.11 g of powder.
[0036] Example 3
[0037] Bimidazole powder (4 mmol) and tetrafluoroterephthalonitrile powder (4 mmol) were added to a reaction vessel containing 50 g NMP solvent and reacted at 180 °C for 16 hours. After the reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, the precipitate was washed three times with DMF, and then dried to obtain 0.2 g of powder.
[0038] Example 4
[0039] Bimidazole powder (8 mmol) and tetrafluoroterephthalonitrile powder (4 mmol) were added to a reaction vessel containing 100 g of DMF solvent and reacted at 150 °C for 20 hours. After the reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, the precipitate was washed three times with DMF, and then dried to obtain 0.25 g of powder.
[0040] Example 5
[0041] Bimidazole powder (8 mmol), tetrafluoroterephthalonitrile powder (4 mmol), and triethylamine (1 g) were added to a reaction vessel containing 100 g of DMF solvent and reacted at 150 °C for 20 hours. After the reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the precipitate was washed three times with DMF and dried to obtain 0.19 g of powder.
[0042] Example 6
[0043] Bimidazole powder (8 mmol), tetrafluoroterephthalonitrile powder (4 mmol), and pyridine (5 g) were added to a reaction vessel containing 60 g of DMF solvent and reacted at 150 °C for 20 hours. After the reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the precipitate was washed three times with DMF and dried to obtain 0.36 g of powder.
[0044] The materials prepared in Examples 1-6 above were tested, and the results are as follows:
[0045] Photos of the bisimidazole-substituted terephthalonitrile conjugated crystal materials prepared in Examples 2, 4, and 6 are shown below. Figure 1 As shown, with changes in reaction conditions, all the obtained samples were powdery solids, but their colors varied. Specifically, the sample obtained in Example 2 was a reddish-brown powder, the sample obtained in Example 4 was a brownish-green powder, and the sample obtained in Example 6 was a dark green powder. The different shades of color indicate that the materials have varying absorption capacities for visible light.
[0046] Scanning electron microscope (SEM) images of the samples from Examples 1 to 6 are shown below. Figure 2 As shown.
[0047] As shown in the figure, the bisimidazole-substituted terephthalonitrile conjugated crystal materials prepared by this invention all exhibit a lamellar crystal structure with a relatively regular layered stacking morphology. The morphology varies slightly between different embodiments. The sample obtained in Example 2 has a more complete lamellar structure and more obvious layered steps; please refer to [link to example]. Figure 3 , Figure 3 The optical microscope revealed relatively perfect, ultra-large grains. The sample obtained in Example 4 showed more uniform lamellar structures, with some lamellars slightly peeling off to form a thinner layered structure. The sample obtained in Example 6 still maintained regular lamellar crystals, but the lamellar surfaces were denser, with a small number of fine particles adhering locally. Overall, the materials obtained in each example possessed stable lamellar microstructures, providing a good structural basis for applications such as electron transport, photothermal conversion, and polymer composite reinforcement.
[0048] The materials prepared in Examples 1-6 were then put into practical applications:
[0049] Application Example 1
[0050] The bisimidazole-substituted terephthalonitrile conjugated crystal material prepared in Example 2 was subjected to ultrasonic exfoliation and dispersion to obtain micro / nano single-crystal wafers. Single-crystal X-ray diffraction was performed on the obtained single-crystal wafers to obtain their crystal structure and unit cell parameters. Using the experimental crystal structure as an initial model, the geometry was optimized using the CASTEP module in Materials Studio software. The band structure and density of states were calculated based on the optimized crystal structure. The calculation results show that the material has a band gap of approximately 1.4 eV. (See [link to relevant documentation]). Figure 4 The valence band and conduction band are continuously distributed, exhibiting obvious semiconductor band characteristics, indicating that the material prepared by this invention has good electron transport potential and can be used as an organic semiconductor material in organic field-effect transistors, photodetectors, organic solar cells, flexible electronic devices and related optoelectronic functional devices.
[0051] Application Example 2
[0052] The diimidazole-substituted terephthalonitrile conjugated crystal materials prepared in Examples 2, 4, and 6 were subjected to thermogravimetric analysis (TGA) under nitrogen and air atmospheres, respectively, to evaluate their thermal stability. The test results show that under nitrogen atmosphere, [see [reference needed]]. Figure 5 Both Examples 2 and 4 exhibited high thermal stability and retained a certain char content even at high temperatures. Specifically, Example 4 showed a residual mass of approximately 61% at 800°C, while Example 2 showed a residual mass of approximately 44% at 800°C. In contrast, the raw materials tetrafluoroterephthalonitrile and biimidazole showed significant weight loss around approximately 190°C and 340°C, respectively, indicating that the thermal stability of the material was significantly improved after the formation of a conjugated aromatic heterocyclic framework via coupling reaction.
[0053] Please refer to the air atmosphere. Figure 5 Examples 2, 4, and 6 also exhibited excellent thermal oxidation stability. All three materials showed significant thermal oxidation weight loss only above approximately 500°C, indicating good heat oxidation resistance in air. Specifically, the residual masses of Examples 6, 4, and 2 at 800°C were approximately 58%, 50%, and 35%, respectively. These results demonstrate that the bisimidazole-substituted terephthalonitrile conjugated crystal material prepared in this invention possesses a rigid aromatic heterocyclic conjugated framework and strong intermolecular interactions, maintaining good structural stability under high-temperature conditions. It can be used as a high-heat-resistant organic functional material or heat-resistant filler in high-temperature composite materials, heat-resistant coatings, and photothermal conversion materials.
[0054] Application Example 3
[0055] The bisimidazole-substituted terephthalonitrile conjugated crystal materials prepared in Examples 2, 4 and 6 were respectively laid flat on stainless steel sheets and continuously irradiated with LED ultraviolet lamps for 300 seconds at an irradiation power density of 9 W / cm². At the same time, a thermal imager was used to collect temperature data at a distance of about 20 cm from the material.
[0056] Test results show that the bisimidazole-substituted terephthalonitrile conjugated crystal material prepared in this invention exhibits excellent photothermal conversion performance. After ultraviolet irradiation, the material can respond rapidly and heat up quickly within 1 second. Specifically, the highest surface temperatures of samples in Examples 2, 4, and 6 reached approximately 212.9℃, 236.1℃, and 230.1℃ after 1 second of irradiation, respectively; after 4 seconds of irradiation, the highest temperatures further increased to approximately 325.6℃, 369.2℃, and 360.3℃, respectively, indicating that the material can efficiently convert light energy into heat energy in a very short time and achieve rapid heating. Please refer to [link to relevant documentation]. Figure 6 .
[0057] Even with the irradiation time extended to 300 s, the sample maintained a relatively high temperature. Experimental observation revealed only slight scorching marks on the surface of the powder layer. Please refer to [link to relevant documentation]. Figure 7 The internal main structure remained intact, and no obvious smoke was observed during the test, nor was any open flame combustion observed. This indicates that the material of the present invention has good high temperature resistance and thermal stability, and can still maintain good structural stability under high temperature and light-heat environment.
[0058] The bisimidazole-substituted terephthalonitrile conjugated crystal material prepared in this invention possesses a highly conjugated multi-aromatic heterocyclic framework structure and a high nitrogen atom content. It exhibits an abundant π-electron delocalization system within the molecule, which enhances light absorption and promotes non-radiative transitions from light to heat energy. Simultaneously, the rigid aromatic heterocyclic conjugated structure endows the material with excellent thermal stability, making it resistant to violent decomposition and combustion under high-temperature irradiation conditions. Therefore, this material possesses excellent photothermal conversion capabilities and high-temperature resistance, making it applicable to fields such as photothermal conversion, localized heating, photothermal catalysis, high-temperature protection, and heat-resistant composite materials.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material, characterized in that, Includes the following steps: Biimidazole and tetrafluoroterephthalonitrile in a molar ratio of 0.5:1 to 4:1 are added to a solvent for a solvothermal reaction, wherein the total mass of the solute is 0.5% to 5% of the mass of the solvent. After the reaction was completed, the mixture was cooled to room temperature, the supernatant was removed, the precipitate was collected, washed with solvent, and dried to obtain a bisimidazole-substituted terephthalonitrile conjugated crystal material.
2. The method for preparing the high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material according to claim 1, characterized in that, The solvent is N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP).
3. The method for preparing the high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material according to claim 1, characterized in that, The solvothermal reaction is carried out at a temperature of 100-200℃ for 4-20 hours.
4. The method for preparing the high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material according to claim 1, characterized in that, In addition, organic additives are added to the solvothermal reaction to regulate the crystal morphology, molecular packing and thermal stability of the material. The organic additives are one or more of pyridine, triethylamine, ammonia, imidazole, dimethylimidazolium, quinoline and piperidine.
5. The method for preparing the high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material according to any one of claims 1-4, characterized in that, The prepared bisimidazole-substituted terephthalonitrile conjugated crystal material has a plate-like crystal or layered stacked structure, and only exhibits significant thermal oxidation weight loss at temperatures above 500 °C in air.
6. The method for preparing the high-temperature resistant bisimidazole-substituted terephthalonitrile conjugated crystal material according to claim 5, characterized in that, The bisimidazole-substituted terephthalonitrile conjugated crystal material is used in the fields of organic semiconductors, photoelectric detection, photothermal conversion, solar thermal utilization, heat-resistant coatings, flame-retardant fillers, or heat-resistant composite materials.